Heart lung transplantation in a patient with end stage lung disease due to common variable immunodeficiency. Issue 7 (1st July 1998) - Hill, A T; Thompson, R A; Wallwork, J; Stableforth, D E
Abstract : The case history is presented of a patient with common variable immunodeficiency in whom heart lung transplantation has been carried out with success. Transplantation was the only long term therapeutic option in this patient due to the progressive respiratory failure resulting from bronchiectasis, emphysema, and granulomatous lung disease.